Killer presentations with your iPad: how to engage your audience and win more business with the world's greatest gadget - Anthony, Ray.; LeVitus, Bob. (New York : McGraw-Hill, 2014)
'Create innovative presentations with the world's greatest communication tool. Killer Presentations with Your iPad enables presenters of all levels to ditch their tired old slides and bullet points and, instead, reimagine and reinvent their presentations with stunning results. The authors describe how to engage audiences with compelling videos, real-time data, specific apps and hardware, and they explain how to leverage presentation skills to this new, exciting format. The book includes a breakthrough model called P-XL2 (superscript) of Technology, Strategy, Creativity, and Psychology that will give your presentation an enormous winning advantage. It also includes a comprehensive resource section along with valuable examples, case studies, scripts, and checklists.Ray Anthony is the author of six business books and has taught presentations skills to thousands of people over his 25 years as a corporate trainer, executive coach and mentor, garnering rave reviews. Bob LeVitus has been considered one of the world's leading authorities on the Macintosh and Mac OS for over 25 years'--
Includes index.
Keywords: Business presentations; iPad (Computer) -- Handbooks, manuals, etc